2021
DOI: 10.1016/j.xpro.2020.100236
|View full text |Cite
|
Sign up to set email alerts
|

IFI16 knockdown in primary HIV-1 target cells

Abstract: Summary IFI16 is an important player of the host intrinsic immune response. Among others, it has been reported to sense intermediate products of HIV-1 reverse transcription in the cytosol and to sequester the transcription factor Sp1 in the nucleus to attenuate viral gene expression. Here, we present three different methods to reduce IFI16 protein expression levels in HIV-1 primary target cells. These techniques can be adapted for the investigation of other cellular factors in primary macrophages an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…We found that endogenous IFI16 expression reduces infectious HIV-1 CH058 yield in primary CD4 + T cells by more than an order of magnitude (Figure 6). This result most likely still underestimates the inhibitory effect of IFI16 on susceptible primary HIV-1 strains since the average frequency of IFI16 KO cells achieved by treatment with Cas9 and IFI16-specific gRNA was just $70% (Bosso et al, 2020a(Bosso et al, , 2020b. Introduction of the additional NF-kB site that is characteristic for subtype C strains conferred almost full resistance to this inhibitory mechanism.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…We found that endogenous IFI16 expression reduces infectious HIV-1 CH058 yield in primary CD4 + T cells by more than an order of magnitude (Figure 6). This result most likely still underestimates the inhibitory effect of IFI16 on susceptible primary HIV-1 strains since the average frequency of IFI16 KO cells achieved by treatment with Cas9 and IFI16-specific gRNA was just $70% (Bosso et al, 2020a(Bosso et al, , 2020b. Introduction of the additional NF-kB site that is characteristic for subtype C strains conferred almost full resistance to this inhibitory mechanism.…”
Section: Discussionmentioning
confidence: 94%
“…A third NF-kB site renders HIV-1 resistant to IFI16 restriction in CD4 + T cells IFI16 is efficiently expressed in CD4 + T cells (Bosso et al, 2020a;Hotter et al, 2019) representing the main target cells for HIV-1 replication in vivo. Using a previously established protocol (Bosso et al, 2020b), we depleted IFI16 expression in CD4 + T cells by nucleofection of CRISPR-Cas9 complexes containing IFI16-specific guide RNAs (gRNAs) (Figure 6A). In agreement with previous data (Bosso et al, 2020a;Hotter et al, 2019), partial knockout (KO) of IFI16 in primary CD4 + T cells increased infectious yield of the HIV-1 subtype B CH058 IMC about 10-fold but had little effect on the HIV-1 subtype C CH185 IMC (Figure 6B).…”
Section: Determinants Of Hiv-1 Subtype B Thro Resistance To Nuclear Pyhin Proteinsmentioning
confidence: 99%
“…Viral transcript quantity was determined as previously described ( 68 ). Briefly, HEK293T cells were cotransfected with proviral constructs of either NL4-3, CH077 TF, or CH077 CC and increasing doses of expression constructs for PTMA .…”
Section: Methodsmentioning
confidence: 99%